Baleen whale acoustic presence and behaviour at a Mid-Atlantic migratory habitat, the Azores Archipelago - Romagosa, Miriam; Baumgartner, Mark; Cascão, Irma; Lammers, Marc O.; Marques, Tiago A.; Santos, Ricardo S.; Silva, Mónica A. (Scientific Reports, 2020)
This work was supported by Fundação para a Ciência e Tecnologia (FCT), Azores 2020 Operational Programme and Fundo Regional da Ciência e Tecnologia (FRCT) through research projects TRACE (PTDC/MAR/74071/2006), MAPCET (M2.1.2/F/012/2011) and AWARENESS (PTDC/BIA-BMA/30514/201), co-funded by FEDER, COMPETE, QREN, POPH, ERDF, ESF, the Lisbon Regional Operational Programme, and the Portuguese Ministry for Science and Education. Funding for publication fees was provided by Project AWARENESS (PTDC/BIA-BMA/30514/201). Okeanos R&D Centre is supported by FCT, through the strategic fund (UIDB/05634/2020). MR was supported by a DRCT doctoral grant (M3.1.a/F/028/2015) and MAS by an FCT-Investigator contract (IF/00943/2013). TAM thanks partial support by CEAUL (funded by FCT - Fundação para a Ciência e a Tecnologia, Portugal, through the project UID/MAT/00006/2013). The identification of important areas during the annual life cycle of migratory animals, such as baleen whales, is vital for their conservation. In boreal springtime, fin and blue whales feed in the Azores on their way to northern latitudes while sei whales migrate through the archipelago with only occasional feeding. Little is known about their autumn or winter presence or their acoustic behaviour in temperate migratory habitats. This study used a 5-year acoustic data set collected by autonomous recorders in the Azores that were processed and analysed using an automated call detection and classification system. Fin and blue whales were acoustically present in the archipelago from autumn to spring with marked seasonal differences in the use of different call types. Diel patterns of calling activity were only found for fin whales with more calls during the day than night. Sei whales showed a bimodal distribution of acoustic presence in spring and autumn, corresponding to their expected migration patterns. Diel differences in sei whale calling varied with season and location. This work highlights the importance of the Azores as a migratory and wintering ...